Avanços e contradições da política de educação profissional integrada no Paraná (2003-2010) - Saldanha, Leticia de Luca Wollmann (2010)
This research presents an analysis of the development of the Professional Education Policy in Paraná (both regarding its conception and actions) from 2003 to 2010. Based upon the historical and dialectical materialism, the research aimed to investigate the historical, legal, political and economic determinations involving both structural and short-term conditions, as well as their meaning to social and educational projects dated from the 20th century and currently under debate. Gramsci’s concepts of extended State and intellectual (1987; 2001) and Löwy’s concept of ideology (2007) were used as theoretical bases. The research methodology consisted of a bibliographical research on ideas presented by Frigotto, Ciavatta and Ramos (2005); an analysis of the document “Political and Pedagogical Bases for Professional Education” (PARANÁ, 2005) and other documents containing quantitative and qualitative data related to the state of Paraná; an analysis of the national laws and an interview with the head of the Department of Education and Work. The Integrated Professional Education Policy in Paraná retrieves the primary concept of polytechnic education supported by part of the civil society in the 1980s.The political society (government), for its part, has an understanding of human education that reveals an ideology (world view) characterised by criticism towards capitalism and a counter-hegemonic orientation – represented by actions carried out by intellectuals and members of the organised civil society – towards the conservative liberalism of the 1990s. Being part of the Brazilian reality and the contradictory relations amongst work, education and capital, the aforementioned policy synthesises the humanisation and work training process, which is mediated by historical, social, scientific and technological knowledge. Furthermore, its conception and resumption represent an advance, but its structural limitations – for instance, the lack of a financing policy that provides permanent maintenance and development for educational activities – need to be addressed so that it can take effect as a public policy.